Exploring challenges with transfer pricing in South Africa: impact on government spent and income - Mashamaite, Mmapula (Graduate School of Business (GSB), 2025)
Transfer pricing is a challenge for tax collection as taxpayers in multinational corporations may shift profits from affiliates in high-tax jurisdiction to their lower-tax jurisdiction counterparts (for tax avoidance), leading to reduced tax collected and therefore the country's financial muscle weakened. Transfer pricing practices have been found, to be responsive to opportunities for avoiding payment of public taxes, as a result this research explored the challenges that the South African government faces relating to transfer pricing transactions. The research undertook in-depth interviews with seven taxation professionals and analysed the data usingqualitative thematic analysis. The thematic analysis revealed several critical themes for each of the three research objectives. Firstly, for the objective of examining the main transfer pricing challenges in South Africa, the complexity of transfer pricing rules, prolonged transfer pricing audit processes, multinational enterprises (MNEs) obedience to transfer pricing rules, and skills shortages were revealed as the key themes. Advanced South African Revenue Services (SARS) reporting systems, advance pricing agreements enforcement, assistance by development finance institutions, improved technological resource capabilities, and capacity and resource improvements were revealed as key themes for the objective of exploring the initiatives employed by South Africa to address the transfer pricing challenges. Lastly, in understanding the key challenges experienced by SARS in collecting tax revenues from transfer pricing transactions, it was revealed that access to relevant MNE information, the complexity of transfer pricing transactions, inadequate transfer pricing transaction tax reporting, disputes raised by MNE's on transfer pricing assessment outcomes, and skills shortages were the main themes. The data presented in this paper is in more ways affirmative, as the trajectory from both tax professionals with knowledge and experience within SARS and those with both SARS and MNE knowledge has been sourced. This paper documents the key challenges that South Africa and its revenue authority, SARS, face concerning taxes on arm's length transactions. The paper further indicates initiatives that should be considered to address these challenges; however, there is still a need for a clearer understanding of the skills requirements for effective management of the taxes from arm's length transactions.